Investigation of enhanced CO2 storage in deep saline aquifers by WAG and brine extraction in the Minnelusa sandstone, Wyoming. (15th February 2023) - Wang, Heng; Kou, Zuhao; Ji, Zemin; Wang, Shouchuan; Li, Yunfei; Jiao, Zunsheng; Johnson, Matthew; McLaughlin, J. Fred
Abstract: Geological CO2 sequestration in deep saline aquifers has been extendedly investigated to reach the goal of carbon neutral as large amount of CO2 can be reduced in a short time. This study investigates the feasibility of water-alternating-gas (WAG) injection and brine extraction on enhancing CO2 storage in a target deep saline aquifer, Minnelusa Sandstone in the Powder River Basin (PRB) of Wyoming. An integrated numerical model is developed to account for four scenarios: (1) CO2 continuous injection (CI) through one injection well, (2) WAG injection through one injection well, (3) CO2 CI through one injection well and brine extraction through one producer, (4) WAG injection through one injection well and brine extraction through one producer. Simulation results suggest that WAG injection and brine extraction corporately make it possible to enhance CO2 injectivity while securing CO2 storage safety. For instance, WAG injection considerably reduces structural trapping contribution while enhances dissolved and residual trapping contributions. As for brine extraction, it can decrease the maximum averaged reservoir pressure by 37% and 22% for CI and WAG injection, respectively. Besides, sensitive analyses of the operational parameters for the fourth scenarios are performed. Results reveal that, when the amount of total CO2 injection has been predetermined, CO2 injection time and rate within each period of WAG should be small whereas it is preferable to have large water injection time and rate. This is to secure desirable dissolved and residual trapping contributions (store CO2 with safety). Sensitive degree results confirm that CO2 injection rate, water injection time, and CO2 injection time of WAG injection exhibit significant effects on CO2 storage whereas the impacts of producer bottom-hole pressure (BHP), water injection rate, and CO2 -water injection time are relatively weaker. This study not only sheds light on achieving double-win goal: enhance CO2 injectivity and store CO2 with safety, but also can be a critical reference for other CO2 storage in deep saline aquifers. Highlights: Geological model-based numerical simulations on CO2 injection into a real saline aquifer are performed. Water-alternating-gas injection increases CO2 dissolved and residual trapping contributions. Brine extraction through producer makes it possible to enhance CO2 injectivity. Major parameters affecting CO2 trapping contribution and CO2 injectivity are screened.